2021
DOI: 10.1186/s12889-021-10176-2
|View full text |Cite
|
Sign up to set email alerts
|

Linking political exposures to child and maternal health outcomes: a realist review

Abstract: Background Conceptual and theoretical links between politics and public health are longstanding. Internationally comparative systematic review evidence has shown links between four key political exposures – the welfare state, political tradition, democracy and globalisation – on population health outcomes. However, the pathways through which these influences may operate have not been systematically appraised. Therefore, focusing on child and maternal health outcomes, we present a realist re-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…From a political epidemiologic perspective, we argue that the social determinants of health are largely affected by political forces (Barnish et al, 2018 , 2021 ; Rodriguez, 2019 ). We observe that there is no social determinant of health that is not preceded by a set of policies and programs prescribed by politicians and that is at least initially provisioned by and executed through the governmental apparatus.…”
Section: Objectivesmentioning
confidence: 99%
“…Colonialism, too, has been identified as a source of adverse health outcomes and health inequalities that negatively affect (racialized) colonial and former colonial subjects and Indigenous peoples across the globe (Bashford 2003, Czyzewski 2011, Ramos et al 2022). An older line of research, but with recent additions relevant to a political economy understanding of health, concerns the adverse impact of dependency relations and globalization on health in the Global South, and on health inequities between populations in the Global North and South (Barnish et al 2021, Forster et al 2020, Labonté et al 2011. Neoliberal policies, policy paradigms, power relations, and ideas have also been identified as sources of health inequalities, both in a global context and within rich democracies (Friel et al 2021, Lynch 2020, Schrecker 2016, Sparke 2017.…”
Section: Structural Determinants Of Healthmentioning
confidence: 99%